Optimal aerobic exercise dose for pain relief in fibromyalgia syndrome: a systematic review and meta-analysis - Li, Yiqi; Yuan, Yuan; Hua, Lijun; Ran, Linghua; Qiu, Bopeng; Yang, Yong; Zhang, Lin (Frontiers in Physiology, 2025)
BackgroundFibromyalgia syndrome (FMS) is a chronic disorder marked by widespread pain. While aerobic exercise (AE) is widely recommended, its isolated effect and the optimal regimen and dose remain unclear. This study aimed to clarify the independent effect of pure AE on pain in FMS and identify the most effective exercise parameters and dose-response relationship.MethodsWe systematically searched PubMed, Cochrane, Embase, and Web of Science up to June 2025 for randomized controlled trials (RCTs) examining AE’s effect on FMS pain. Subgroup analyses were performed by age, baseline pain level, exercise type, and protocol characteristics. Standardized mean differences (SMD) with 95% confidence intervals (CIs) were calculated, and dose–response relationships were explored.ResultsFourteen RCTs with 777 participants were included. AE significantly reduced pain compared with controls [SMD = −1.07; 95% CI: −1.57 to −0.57], especially in patients aged 45–60 years and those with chronic severe pain. The most effective intervention was moderate-intensity, water-based AE performed for 60 min per session, 1–2 times weekly, over 12–16 weeks. Dose–response analysis identified an optimal dose of 470 MET-min/week [SMD = −1.71; 95% CrI: −1.90 to −1.14], with an effective range of 75–750 MET-min/week.ConclusionThis meta-analysis confirms the efficacy of AE in reducing pain in FMS. AE significantly alleviates pain in fibromyalgia, with moderate-intensity, water-based, showing the most effective results. These findings provide strong evidence for incorporating AE as a key non-pharmacological strategy in the management of fibromyalgia, especially for patients with more severe pain. The identified optimal exercise parameters offer clear guidance for clinical practice, supporting the use of tailored exercise regimens in patient care.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/, identifier CRD420251086595.